2014
DOI: 10.1111/gcbb.12227
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative genetic parameters of agronomic and quality traits in a global germplasm collection reveal excellent breeding perspectives for Jatropha curcas L.

Abstract: Jatropha curcas L. (jatropha) is an undomesticated plant, which has received great attention in recent years for its potential in biofuel production and in greening and rehabilitation of wastelands. Yet the absence of improved cultivars and the lack of agronomic knowledge are limiting factors for successful jatropha cultivation. The objectives of the present study were to investigate the perspectives of a worldwide jatropha breeding program and specifically to (i) estimate variance components and heritabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…On the other hand, oil content in seeds harvested at the dry-subhumid site (42.6% in the set of common genotypes) was significantly higher than that in seeds at the humid site (35.2% in the set of common genotypes). Previous studies indicated a strong influence of the environment on seed yields and oil content [7] and a relation of higher protein content in seeds harvested in humid environments to increased nitrogen uptake due to better water availability [19]. The results of the present study further underpin the need for further research on the environmental factors that determine seed and oil yield in jatropha.…”
Section: Effects Of Locations and Yearssupporting
confidence: 64%
See 2 more Smart Citations
“…On the other hand, oil content in seeds harvested at the dry-subhumid site (42.6% in the set of common genotypes) was significantly higher than that in seeds at the humid site (35.2% in the set of common genotypes). Previous studies indicated a strong influence of the environment on seed yields and oil content [7] and a relation of higher protein content in seeds harvested in humid environments to increased nitrogen uptake due to better water availability [19]. The results of the present study further underpin the need for further research on the environmental factors that determine seed and oil yield in jatropha.…”
Section: Effects Of Locations and Yearssupporting
confidence: 64%
“…Canopy management is an important aspect in older jatropha stands, which can be addressed by partial plant elimination and/or pruning [4,20], depending on agro-ecological conditions and plant architecture. Pruning, however, can lead to plant stress and therefore to a reduction of productivity [7,21]. In the long run, varieties with reduced plant height or canopy diameter will be developed that should facilitate harvesting and canopy management practices.…”
Section: Effects Of Establishment Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the large variation for oil content, the oil yield per hectare is not well associated with that trait [11]. Therefore, selection for oil content at early stages of a jatropha breeding program does not correspond with high oil yield per hectare.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, selection for oil content at early stages of a jatropha breeding program does not correspond with high oil yield per hectare. Selection for seed yield and stability has been indicated to achieve rapid and large selection gains [11]. Improvement of oil content could be achieved by recurrent selection cycles within genetic pools and also by inter-pool hybridization.…”
Section: Discussionmentioning
confidence: 99%